Simulation of IR, Raman and VCD amide I band profiles of self-assembled peptides. Issue 1 (2010) - Schweitzer-Stenner Schweitzer-Stenner, Reinhard Reinhard; Measey Measey, Thomas J. Thomas J.
Abstract : Vibrational spectroscopy is a suitable and convenient tool to probe the self-assembly of peptides, a biomedically and biotechnologically relevant process. Theoretical efforts to quantitatively analyze vibrational spectra of peptide aggregates have thus far focused on exploring the IR and to a lesser extent the vibrational circular dichroism (VCD) spectra of rather small sized planar or nearly planar β -sheet structure. The current study utilizes an algorithm based on an excitonic coupling model with experimentally or computationally determined parameters to simulate the amide I band profiles of the IR, isotropic Raman, anisotropic Raman and VCD spectra of two- and three-dimensional β -sheet structures. In agreement with earlier calculations we found that the splitting between the two prominent IR bands of an antiparallel β -sheet increases with increasing number of strands until a saturation is reached at approximately eight strands. The dominant isotropic and anisotropic Raman bands of amide I are located between the two IR bands and downshift only slightly with increasing sheet length. The VCD signal is rather weak. We also investigated the influence of sheet stacking on amide I by calculating the respective IR, Raman and VCD profiles for two in-register, facially stacked β -sheets with seven strands per sheet for an antiparallel arrangement of the sheets and six strands per sheet for a parallel arrangement. We found that stacking produces additional bands in the IR and Raman spectrum, in line with the reduced symmetry of the ideal unit cell of the β -sheet. In addition, a more pronounced VCD signal is detected. A comparison with experimental IR, Raman and VCD spectra of gelated (AAKA)4 reveals a good qualitative agreement between experimental and simulated amide I band profiles.